2016
DOI: 10.1002/etc.3261
|View full text |Cite
|
Sign up to set email alerts
|

Press or pulse exposures determine the environmental fate of cerium nanoparticles in stream mesocosms

Abstract: Risk-assessment models indicate that stream ecosystems receiving municipal wastewater effluent may have the greatest potential for exposure to manufactured nanoparticles. The authors determined the fate of cerium oxide (CeO2 ) nanoparticles in outdoor stream mesocosms using 1) 1-time pulse addition of CeO2 nanoparticles, representative of accidental release, and 2) continuous, low-level press addition of CeO2 nanoparticles, representative of exposure via wastewater effluent. The pulse addition led to rapid nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Luoma, University of California, Davis, Davis, CA, USA, unpublished manuscript), depending on the nature of the NM, the organism, and the media. However, mesocosm dosing also affected outcomes with lower concentrations over time, resulting in more suspended NMs compared with single high doses (Baker et al 2016), in agreement with concentration-dependent laboratory studies (Merrifield et al 2017a). The agreement between mesocosm and laboratory data is encouraging where it happens, but further work is needed to rationalize data where they do not agree.…”
Section: Mesocosm Studiessupporting
confidence: 73%
“…Luoma, University of California, Davis, Davis, CA, USA, unpublished manuscript), depending on the nature of the NM, the organism, and the media. However, mesocosm dosing also affected outcomes with lower concentrations over time, resulting in more suspended NMs compared with single high doses (Baker et al 2016), in agreement with concentration-dependent laboratory studies (Merrifield et al 2017a). The agreement between mesocosm and laboratory data is encouraging where it happens, but further work is needed to rationalize data where they do not agree.…”
Section: Mesocosm Studiessupporting
confidence: 73%
“…Analogously, ENPs are also expected to rapidly transform from their pristine form, due to for example dissolution, agglomeration, sedimentation, and coating alterations once discharged into the environment (Lowry et al, 2014) or even when added to simplified media in laboratory toxicity tests (Petersen et al, 2014). A study of stream mesocosms has found the fate of cerium oxide ENPs to differ for press and pulse exposures and the authors recommend environmental risk assessment of ENPs to address the implications of exposure duration (Baker et al, 2016). To date, several studies have investigated the chronic effects in 6 crustaceans exposed to ENPs of silver (Blinova et al, 2013;Gaiser et al, 2011;Mackevica et al, 2015;Pokhrel and Dubey, 2012;Seitz et al, 2015;Zhao and Wang, 2011), TiO 2 (Seitz et al, 2013), ZnO (Adam et al, 2014;Zhao et al, 2012), and CuO (Adam et al, 2015;Rossetto et al, 2014;Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the size of the aggregates could not be determined by DLS analyses, but nTiO 2 are already known to form aggregates in various natural aqueous matrices, including river water (Keller et al 2009). Thus, the interaction with suspended organic matter in the river water flowing through the artificial habitat could have led to coating and stabilization of nanoparticles (Baker et al 2016). After initial pulse, nTiO 2 could have aggregated with the medium (river water, as quantified by Z potential), with the algae that are used to feed the H. exocellata, on the inner walls of the plastic trays, on the polystyrene blocks of the experimental setup, with humic substances, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, available studies have focused on acute or chronic exposures to nTiO 2 but there is no information on pulse exposures, which could occur when ENMs are released from a hypothetical accidentally municipal wastewater effluent to discharge to rivers and streams (Baker et al 2016). In our study, we used the net-spinning caddisfly Hydropsyche exocellata Dufour, 1841 (Trichoptera, Hydropsychidae) as a model organism to evaluate the potential toxic effects of nTiO 2 pollution on lotic organisms.…”
mentioning
confidence: 99%